PENERAPAN ALGORITMA DIJKSTRA PADA APLIKASI JASA TRANSPORTASI ONLINE DI KOTA MEDAN - abdul alfattah hidayah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study aims to determine the shortest route in the application of online transportation services which is the main attraction for entrepreneurs who want to start looking for their fortune in technology and transportation, given the enormous opportunity where the human population is very large. increased, and some human activities had to be carried out. fulfilled. Some online transportation service companies use paid features provided by Google to determine the shortest distance and route, thus costing a lot of money. In this study, to determine the shortest route on a journey, it is necessary to calculate using an algorithm method, namely the dijkstra algorithm which is an algorithm used to solve the problem of the shortest route or the shortest path from one point to another at a point. weighted graph, The distance between vertices is the weight value of each edge in the graph. A graph that has a weight must be positive (weight >= 0). Dijkstra's algorithm itself uses a greedy strategy in its operation, where in each step the chosen one with the smallest weight connects the selected node with other nodes that have not been selected. Keywords: dijkstra algorithm, online transportation service, shortest route,